From owning to sharing: understanding the emergence of social sharing services. Issue 2 (4th July 2017) - Kim, Heetae; Choi, Kyu Ha; Kim, Ki Joon; Park, Eunil
Abstract : Purpose: The purpose of this paper is to identify the motivational factors that help shape user perceptions of and attitudes toward car-sharing services and develop a research model that integrates these factors with the technology acceptance model to explicate car sharing's adoption pattern. Design/methodology/approach: An online survey was administered to examine the role of proposed motivational factors for the adoption of wearable healthcare devices. Confirmatory factor analysis and structural equation modeling were conducted on collected data ( n =638) to demonstrate the reliability and validity of the measurement and structural model. Findings: Perceived reliability, compatibility, and enjoyment of car-sharing services as well as users' innovative tendencies are positively associated with usage intention. However, users' privacy concern and perceived cost of using the services are found to have no significant effects on the adoption of the services. Originality/value: While the recent advent of mobile communication devices and services has increased access to social sharing-based platform services such as car sharing, this study provides a research framework that helps to understand how various psychological factors contribute to the adoption of a social-sharing service.